Theoretical Investigation on Structure-Property Relationship of Asymmetric Clusters (CH3FBN3)n (n = 1– 6) - Deng-Xue Ma; Yao-Yao Wei; Yun-Zhi Li; Guo-Kui Liu; Qi-Ying Xia (Journal of Chemistry)
The structural, relative stability, electronic, IR vibrational, and thermodynamic properties of asymmetric clusters (CH3FBN3)n (n = 1–6) are systematically investigated using density functional theory (DFT) method. Results show that clusters (CH3FBN3)n (n = 2–6) form a cyclic structure with a B atom and a Nα atom binding together. Five main characteristic regions are observed and assigned for the calculated IR spectra. The size-dependent second-order energy difference shows that clusters (CH3FBN3)3 and (CH3FBN3)5 have relatively higher stability and enhanced chemical inertness compared with the neighboring clusters. These two clusters may serve as the cluster-assembled materials. The variations of thermodynamic properties with temperature T or cluster size n are analyzed, respectively. Based on enthalpies in the range of 200–800 K, the formations of the most stable clusters (CH3FBN3)n (n = 2–6) from monomer are thermodynamically favorable. These data are helpful to design and synthesize other asymmetric boron azides.